Multi Component Mode and Derivative Spectrophotometric Methods for the Simultaneous Determination of Timolol maleate and Brimonidine Tartrate (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: New multicomponent spectrophotometric methods have been established for the simultaneous determination of timolol maleate and brimonidine tartrate in pharmaceutical formulations (eye drops). Timolol is a propanolamine derivative having non-selective beta-adrenergic antagonist action with antihypertensive action. Brimonidine is used to treat glaucoma, or ocular hypertension and timolol can be used as an antihypertensive and anti-glaucoma agent. Materials and Methods: Shimadzu ultraviolet (UV)-1800 model UV-visible spectrophotometer double beam was used for the present study. The three new methods were developed using phosphate buffer pH 7.0. Results and Discussion: The absorption maxima were found at 295 nm for timolol maleate and 247 nm for brimonidine tartrate, respectively. Linearity was observed 1–120 μg/ml for timolol maleate and 1–60 μg/ml for brimonidine tartrate and the three methods were validated as per the ICH guidelines. Conclusions: The three methods can be used for the determination of timolol maleate and brimonidine tartrate in eye drops.